2017
DOI: 10.1038/s41598-017-15386-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of corneal hysteresis and optic nerve parameters in healthy myopic subjects

Abstract: The association between corneal biomechanical properties and glaucoma is an area of much interest. We determined the relationship between corneal hysteresis (CH) and optic nerve parameters in healthy myopic subjects in the current study. CH was measured with Reichert Ocular Response Analyzer in 108 eyes from 108 healthy myopic subjects. All subjects received retinal nerve fiber layer and optic disc imaging Cirrus HD-OCT, GDx ECC, and Heidelberg Retina Tomograph II. None of the tested optic nerve parameters sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…49,[52][53][54] Park et al 49 report no significant association between CCT, CH, or CRF with the mean RNFL thickness, although after adjustment, CH and RNFL were directly associated (ß = 0.013, P = 0.043) in NTG patients. In studies measuring RNFL using OCT, no association was found between CH and CRF, and RNFL thickness in suspect or confirmed OAG, as well as in healthy myopic eyes, 52,53 except for one study in which the relationship between CH and RNFL thickness was significant (ß = 0.2, P = 0.001) in OAG. 54 The results of our study did not find a significant correlation between the average RNFL thickness and CH or CRF, but did find a correlation with CCT, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…49,[52][53][54] Park et al 49 report no significant association between CCT, CH, or CRF with the mean RNFL thickness, although after adjustment, CH and RNFL were directly associated (ß = 0.013, P = 0.043) in NTG patients. In studies measuring RNFL using OCT, no association was found between CH and CRF, and RNFL thickness in suspect or confirmed OAG, as well as in healthy myopic eyes, 52,53 except for one study in which the relationship between CH and RNFL thickness was significant (ß = 0.2, P = 0.001) in OAG. 54 The results of our study did not find a significant correlation between the average RNFL thickness and CH or CRF, but did find a correlation with CCT, as shown in Table 2.…”
Section: Discussionmentioning
confidence: 98%
“…For hyperopic and for female patients, higher values for CRF have been observed. For highly myopic patients, other studies have registered lower values of the CH and CRF and higher values of IOPcc (Corneal Compensated Intraocular Pressure) and of IOPg (Goldmann Correlated IOP value) compared to the emmetropic, hyperopic patients or patients with medium or low myopia [ 31 - 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of corneal biomechanics has helped us to understand the changes in corneal shape and structure after refractive surgery [1,2]. The corneal stiffness is a recently described index with clinical significance for the detection in patients who are at risk of ectasia development [3,4]. Previous studies have shown that the biomechanical properties of the cornea are correlated with many factors such as central corneal thickness (CCT) and intraocular pressure (IOP) [5,6].…”
Section: Introductionmentioning
confidence: 99%